Identification of Chromosomes and Chromosome Rearrangements in Crop Brassicas and Raphanus sativus: A Cytogenetic Toolkit Using Synthesized Massive Oligonucleotide Libraries - Agrawal, Neha; Gupta, Mehak; Banga, Surinder S.; Heslop-Harrison, JS (Pat) (Frontiers in Plant Science, 2020)
Crop brassicas include three diploid Brassica rapa (AA; 2n=2x=16), B. nigra (BB; 2n=2x=18), B. oleracea (CC; 2n=2x=20) and three derived allotetraploid species. It is difficult to distinguish brassica chromosomes as they are small and morphologically similar. We aimed to develop a genome-sequence based cytogenetic toolkit for reproducible identification of Brassica chromosomes and their structural variations. A bioinformatic pipeline was used to extract repeat-free sequences from the whole genome assembly of B. rapa. Identified sequences were subsequently used to develop four c. 47-mer oligonucleotide libraries comprising 27100, 11084, 9291 and 16312 oligonucleotides. We selected these oligonucleotides after removing repeats from 18 identified sites (500 kb to 1000 kb) with 1997 to 5420 oligonucleotides localized at each site in B. rapa. For one set of probes, a new method for amplification or immortalization of the library is described. oligonucleotide probes produced specific and reproducible in situ hybridization patterns for all chromosomes belonging to A, B, C and R (Raphanus sativus) genomes. The probes were able to identify structural changes between the genomes, including translocations, fusions and deletions. Furthermore, the probes were able to identify a structural translocation between a pak choi and turnip cultivar of B. rapa. Overall, the comparative chromosomal mapping helps understand the role of chromosome structural changes during genome evolution and speciation in the family Brassicaceae. The probes can also be used to identify chromosomes in aneuploids such as addition lines used for gene mapping, and to track transfer of chromosomes in hybridization and breeding programmes.